Effects of solar wind high‐speed streams on the high‐latitude ionosphere: Superposed epoch study. Issue 12 (4th December 2015) - Grandin, M.; Aikio, A. T.; Kozlovsky, A.; Ulich, T.; Raita, T.
Abstract: Solar wind high‐speed streams (HSSs) are the most important source of geomagnetic disturbances during the declining phase of the solar cycle. Their ionospheric response, especially at high latitudes, is not fully understood yet. We carried out a phase‐locked superposed epoch analysis to study the effects of HSSs on the high‐latitude ionospheric F region, using data from the Sodankylä ionosonde ( L = 5.25) during 2006–2008. We found that the F layer critical frequency f o F 2 decreases between 12 and 23 magnetic local time (MLT) in summer and around equinoxes for several days. Our interpretation, supported by numerical estimations, is that increased electric fields in the evening sector of the auroral and subauroral regions create ion‐neutral frictional heating. Frictional heating will increase the loss rate of O + due to two reasons. The first one is neutral heating producing thermal expansion of the atmosphere and enhancing N2 and O2 contents at the F region peak. The second one is ion heating which may occur under strong enough electric fields (about 50–60 mV/m), leading to enhancement of the reaction coefficients. An increase in f o F 2 is observed in two different MLT sectors. First, a short‐lived f o F 2 increase is visible during all seasons near noon on the first day after the arrival of the HSS, possibly triggered by the compressed solar wind plasma pressure pulse, which may produce particle precipitation from the dayside central plasma sheet. Second, f o F 2 is enhanced for several days in the morning sector during equinoxes and in winter. We suggest that this is caused by the low‐energy tail of particle precipitation. Key Points: Solar wind HSSs decrease peak Ne in the evening sector at high latitudes Decrease of F region Ne is caused by ion‐neutral frictional heating HSS‐induced particle precipitation increases peak Ne at noon and in the morning